Implementasi E-Learning Media Pembelajaran Berbasis Website Menggunakan Articulate Storyline dalam Mata Pelajaran DKV - Wardika, Ajis; Ripai, Ipan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to implement web-based interactive learning media using Articulate Storyline 360 in the Visual Communication Design (VCD) subject at SMK Negeri 1 Luragung and to assess its effectiveness on learning outcomes. The method applied was a pre-experimental design with a one group pretest–posttest model, involving 34 tenth-grade VCD students selected through purposive sampling. Instruments included learning achievement tests (pretest and posttest) and validation questionnaires from material and media experts. The data were analyzed using quantitative descriptive methods. The results showed an increase in the average score from 45.2 to 66.6. The paired sample t-test at a 5% significance level indicated Sig. < 0.05, signifying a significant difference before and after treatment. Expert validations categorized the media as “very feasible.” The media was found effective in improving students’ learning outcomes in VCD.